2009
DOI: 10.1002/anie.200805323
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Contact Ion‐Pair Formation in Aqueous Solution

Abstract: The formation of ion pairs in aqueous solution orchestrates vital processes in nature and engineered systems, including electron transfer [1][2][3] and other chemical reactions, [4,5] and crystallization/precipitation of synthetic and natural matter. [6][7][8][9] Polyoxometalates (POMs) have received special attention with regard to ion pairing.[10] POMs are highly charged anions with ideal topologies for binding and associating metal cations, as their assembly, [11][12][13] redox, [2] and catalytic properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 36 publications
(62 reference statements)
8
112
1
4
Order By: Relevance
“…This indicates that potassium ions stabilize the hexaniobate ions HNb 6 O 19 7- (aq) and that the solubility of Na 7 HNb 6 O 19 ·15H 2 O (s) is no more controlled by the common ion effect. The formation of the ion-pairs K 8 Nb 6 O 19(aq) and K 10 Nb 6 O 19 2+ (aq) was observed by Antonio et al (2009) in 3 mol.L -1 KOH based on small-angle X-ray scattering. Hence, ion-pairs formation between K + (aq) and HNb 6 O 19 7-(aq) could explain the increase of the solubility of Na 7 HNb 6 O 19 ·15H 2 O (s) in K + -containing media.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 1 more Smart Citation
“…This indicates that potassium ions stabilize the hexaniobate ions HNb 6 O 19 7- (aq) and that the solubility of Na 7 HNb 6 O 19 ·15H 2 O (s) is no more controlled by the common ion effect. The formation of the ion-pairs K 8 Nb 6 O 19(aq) and K 10 Nb 6 O 19 2+ (aq) was observed by Antonio et al (2009) in 3 mol.L -1 KOH based on small-angle X-ray scattering. Hence, ion-pairs formation between K + (aq) and HNb 6 O 19 7-(aq) could explain the increase of the solubility of Na 7 HNb 6 O 19 ·15H 2 O (s) in K + -containing media.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…Hexaniobate ions are known to form ion-pairs with Cs + (aq) , Rb + (aq) and K + (aq) ions (Antonio et al, 2009;Kinnan et al, 2014). It was recently reported that ion-pairs formation decreases along the series Cs > Rb > K > Na > Li and that Nb 6 O 19 8-(aq) ion does not interact with Li + (aq) ions (Antonio et al, 2009;Kinnan et al, 2014;Fullmer et al, 2014). The sodium case has not been treated in the literature and, consequently, we tried different models to fit our solubility measurements.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Cobalt nitrate (Co(NO 3 43 Different ratios of Co or Ni to Nb (the initial concentrations of Co 2+ or Ni 2+ were kept constant) were also tested for electrodeposition of hydr(oxide), but a 1:1 ratio provided the best deposition efficiency as defined by the largest current per cycle of potential. …”
Section: Methodsmentioning
confidence: 99%
“…16,19,[35][36][37] The species NbO 3 − is a hypothetical species which was mentioned in few solubility studies 38,39 Equilibria involving hexaniobates and other minor species which would be more extractible cannot be excluded, but given the current knowledge on polyoxoniobate chemistry, the extraction of hexaniobates seems the most likely mechanism at a pH higher than ∼10. Therefore, reaction (5) can be considered to be a rational basis to describe the extraction of Nb(V) with methyltrioctylammonium chloride from alkaline media.…”
Section: Solvent Extraction Proceduresmentioning
confidence: 99%
“…Such a conclusion is in accordance with the stability of the alkali-hexaniobate ion-pairs observed in the aqueous systems, which follows the following trend: Li + < Na + < K + < Rb + < Cs + . 31,37,43 The influence of alkali ions on the extraction of hexaniobate ions was further investigated in lithium-, potassium-and cesium-based media, taking the sodium hexaniobate system as a reference. Fig.…”
Section: Influence Of Cations On the Background Electrolytementioning
confidence: 99%